Iron Status of Cats with Chronic Kidney Disease. (29th September 2015) - Gest, J.; Langston, C.; Eatroff, A.
Abstract : Background: Iron deficiency is a proposed mechanism for the anemia that occurs in cats with chronic kidney disease (CKD). Minimal research investigating the iron status of these cats has been performed. Objective: To compare indicators of iron status in cats with CKD versus healthy cats and cats with nonrenal illness (NRI). To compare indicators of iron status in anemic versus nonanemic cats with CKD. Animals: Thiry‐nine client or employee owned healthy cats, 40 cats with CKD and 34 cats with NRI included. Methods: Exclusion criteria included prior iron or erythropoiesis stimulating agent administration, blood transfusion, or concurrent CKD and NRI. Complete blood counts, serum chemistries, serum iron concentrations, total iron binding capacity (TIBC), and ferritin concentrations were measured and percent transferrin saturation (TSAT) calculated on all cats. Data were analyzed using nonparametric statistical testing. Results: No statistically significant differences were detected among groups for iron concentration ( P = .50), ferritin concentration ( P = .47), or TSAT ( P = .19). TIBC was significantly lower in CKD (median 262 μg/dL; IQR 233–302; range 165–488) versus healthy cats (median 316 μg/dL; IQR 272–345, range 196–464); ( P = .0030). When comparing anemic (hemoglobin <9.5 g/dL) versus nonanemic cats with CKD, TSAT was significantly lower ( P = .033) in anemic (median 20.2%; IQR 17.8–34.5; range 17.6–35.9) compared to nonanemic (median 29.0%; IQR 25.5–44.1; range 11.5–94.4). No statistically significant differences found for ferritin concentration ( P = .94), iron concentration ( P = .21) or TIBC ( P = .97). Conclusions and Clinical Importance: These results indicate that an iron deficient state exists in anemic cats with CKD and is more likely functional rather than absolute.